(untitled) (Лучшие интеллектуальные исследования, 2025)
In an increasingly interconnected world, the concept of global citizenship has gained significant importance. As societies become more diverse and global challenges such as climate change, social inequality, and political instability require collective action, education systems must adapt to prepare students for the complexities of the modern world. One such adaptation is the integration of Global Citizenship Education (GCE) into the English as a Foreign Language (EFL) curriculum. This approach not only enhances language skills but also fosters a sense of global responsibility, cultural awareness, and social justice among learners.